Functional Genome Mining Reveals a Class V Lanthipeptide Containing a d‐Amino Acid Introduced by an F420H2‐Dependent Reductase. (18th August 2020) - Xu, Min; Zhang, Fei; Cheng, Zhuo; Bashiri, Ghader; Wang, Jing; Hong, Jiali; Wang, Yemin; Xu, Lijun; Chen, Xuefei; Huang, Sheng‐Xiong; Lin, Shuangjun; Deng, Zixin; et al.
Abstract: Lantibiotics are a type of ribosomally synthesized and post‐translationally modified peptides (termed lanthipeptides) with often potent antimicrobial activity. Herein, we report the discovery of a new lantibiotic, lexapeptide, using the library expression analysis system (LEXAS) approach. Lexapeptide has rare structural modifications, including N‐terminal ( N, N )‐dimethyl phenylalanine, C‐terminal (2‐aminovinyl)‐3‐methyl‐cysteine, and d ‐Ala. The characteristic lanthionine moiety in lexapeptide is formed by three proteins (LxmK, LxmX, and LxmY), which are distinct from enzymes known to be involved in lanthipeptide biosynthesis. Furthermore, a novel F420 H2 ‐dependent reductase (LxmJ) from the lexapeptide biosynthetic gene cluster (BGC) is identified to catalyze the reduction of dehydroalanine to install d ‐Ala. Our findings suggest that lexapeptide is the founding member of a new class of lanthipeptides that we designate as class V. We also identified further class V lanthipeptide BGCs in actinomycetes and cyanobacteria genomes, implying that other class V lantibiotics await discovery. Abstract : Lexapeptide is a lantibiotic showing potent antibacterial activity against Gram‐positive bacteria such as MRSA and MRSE, featured by the lanthionine (Lan) and d ‐Ala formation in its structure. The formation of Lan is catalyzed by a class V lanthionine synthetase comprised of three standalone proteins. The d ‐Ala28 is installed by the F420 H2 ‐dependent reductase LxmJC, which can introduce d ‐stereocenters into lanthipeptides.